01.sinα^2+cosα^2+sinα^2/cosα^2=
1/cosα^2(sinα^2cosα^2+cosα^4+sinα^2)=
1/cosα^2[cosα^2(sinα^2+cosα^2)+sinα^2]=
1/cosα^2(cosα^2+sinα^2)=
1/cosα^2=secα^2
02.cosα^2-2cosα+1+sinα^2=
1+1-2cosα=2-2cosα
03.cosα^2-2cosαcosβ+cosβ^2+sinα^2-2sinαsinβ+sinβ^2
=cosα^2+sinα^2+cosβ^2+sinβ^2-2cosαcosβ-2sinαsinβ
=2-2(cos αcos β+sin αsin β)
04.1-2sinαcosα=
sinα^2-2sinαcosα+cosα^2
=(sinα-cosα)^2
05.sinθcosθ/tanθ=sinθcosθ*cosθ/sinθ=cosθ^2
左边=sinθ^2+cosθ^2+tanθ^2=1/cosθ^2
2.
01.原式=0
02.原式=tanθ+1/tanθ/tanv+1=tanθ
03.原式=1+2sinθ+sinθ^2+cosθ^2/cosθ*(1+sinθ)=2(1+sinθ)/cosθ*(1+sinθ)
=2/cosθ
04.原式=1+sinθ/cosθsinθ+cosθ/sinθ
=sinθ/cosθ=tanθ